1996
DOI: 10.1038/381607a0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of simple-cell receptive field properties by learning a sparse code for natural images

Abstract: The receptive fields of simple cells in mammalian primary visual cortex can be characterized as being spatially localized, oriented and bandpass (selective to structure at different spatial scales), comparable to the basis functions of wavelet transforms. One approach to understanding such response properties of visual neurons has been to consider their relationship to the statistical structure of natural images in terms of efficient coding. Along these lines, a number of studies have attempted to train unsupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

82
3,849
8
26

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 4,875 publications
(3,965 citation statements)
references
References 23 publications
82
3,849
8
26
Order By: Relevance
“…However, a morphed neurons structure is still very similar to its original structure and is similar to other feature detectors that operate on seemingly unrelated features. Such a theory would be in agreement with observations that natural images can be described with a relatively small number of Gabor derived kernels very efficiently (Olshausen and Field 1996). As such one might expect the flora of feature detectors to be somewhat constrained at this level of cortex.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, a morphed neurons structure is still very similar to its original structure and is similar to other feature detectors that operate on seemingly unrelated features. Such a theory would be in agreement with observations that natural images can be described with a relatively small number of Gabor derived kernels very efficiently (Olshausen and Field 1996). As such one might expect the flora of feature detectors to be somewhat constrained at this level of cortex.…”
Section: Discussionsupporting
confidence: 85%
“…The research thus far agrees with work to date that suggests that V1 neurons are extremely powerful for extracting data from a scene (Olshausen and Field 1996). Additionally, it also helps to validate hypotheses that suggest neurons in V1 have a high dimensionality for visual processing.…”
Section: Contours + Junctions Opening a New Dimension On Visual Cortexsupporting
confidence: 84%
“…This principle has proven extremely powerful in predicting some of the basic receptive field properties of cells involved in early visual processing (e.g. Atick and Redlich, 1990;Olshausen and Field, 1996). This principle represents a formal statement of the common sense notion that neuronal dynamics in sensory systems should reflect, efficiently, what is going on in the environment (Barlow, 1961).…”
Section: Information Theoretic Approachesmentioning
confidence: 99%
“…To minimise redundancy one can either minimise the entropy of the output units or maximise their joint entropy, while ensuring the other is bounded in some way. Olshausen and Field (1996) present a very nice analysis based on sparse coding. Sparse coding minimises redundancy using single units with low entropy.…”
Section: Efficiency Redundancy and Informationmentioning
confidence: 99%
“…Recent advances in computational neuroscience have shown that relatively simple models of developmental visual systems are capable of developing qualitatively similar properties to those found in the early stages of visual processing in cats and monkeys (Hancock et al, 1992;Field, 1994;Olshausen and Field, 1996;Rao and Ballard, 1999). However, those models often use images from publicly available databases or photographs taken in a natural environment as visual stimuli, and do not allow the system to freely interact with the environment and choose those sensory events.…”
Section: Introductionmentioning
confidence: 99%